SHAPING OF MORAL PEOPLE TOWARDS LAW COMPLIANCE FROM A WESTERN THEORY PERSPECTIVE - Hairul Faiezi Lokman; Amyza Nyirong Karim; Nur Adlin Nabilah Din; Danisha Theevaheran (Journal Civics And Social Studies, 2022)
A moral person is a personal characteristic of good and bad behavior that stands out and is accepted in the context of society. Obedience to the law is a necessity in the life of an individual who is surrounded by various codes of conduct and ethics to realize a perfect life. Forming moral human beings from various points of view is the foundation and guideline of life. This article discusses the perspective of western theory in shaping legal compliance. As a bibliographic study, this paper presents qualitative findings based on detailed references from journals, articles, books and newspapers. The findings are then explained thematically using narrative writing. Based on research findings, the formation of moral humans towards obeying the law can be carried out through the perspective of three western theories, namely utilitarianism theory, personality virtue and deontological theory. Research findings are also discussed based on examples and descriptions.